DISKRIMINASI GENDER DALAM NOVEL 5 KELOPAK MAWAR BERBISA KARYA RIA JUMRIATI DAN NOVEL KAPAK KARYA DEWI LINGGASARI: KRITIK SASTRA FEMINIS - Roza Muchtar; Nurizzati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
In Indonesian literature, gender issues are frequently the subject of stories and their main focus, such as the societal structures that give rise to a patriarchal culture. Gender discrimination is the product of this patriarchal culture. This study intends to 1) describe gender discrimination against women in Ria Jumriati's novel 5 Kelopak Mawar Berbisa, 2) describe gender discrimination against women in Dewi Linggasari's novel Kapak, and 3) compare gender discrimination against women in the novels 5 Kelopak Mawar Berbisa and Kapak. Descriptive methodology along with content analysis was employed in this study. Feminist literary criticism is used as the analytical instrument in this research, which takes a mimetic approach in keeping with sociology of literature theory. The reading and note-taking method was utilized in this study to obtain data. The data analysis technique was completed in three parts, including (1) classifying and coding the gender discrimination data found in the two novels using a data classification format, (2) interpreting the gender discrimination data found in the two novels, and (3) drawing and formulating conclusions based on the data examined. The findings of this study imply that there are several forms of discrimination against women on the basis of their gender, including aggression, stereotypes, subordination, and double the workload, additionally, there is a similarity between the elements of injustice in the two novels that will give rise to various sorts of gender discrimination.